PEMANFAATAN INTERNET UNTUK RISET DAN IMPLIKASI TERHADAP RISET AKUNTANSI - Didi Achjari (UGM, 2000)
Rapid Development of internet technology can influence the way we do research. Yet there are some weaknesses of research by using internet such as anonymity, demography of respondent, accessibility, risk of plagiarism, and reliability, the benfit is obvious. Accademnc staffs, researchers or students are advantaged since they can use it for referencing tool, on-line database.